Dried-blood-spot technique to monitor direct oral anticoagulants: clinical validation of a UPLC-MS/MS-based assay - Foerster, Kathrin; Huppertz, Andrea; Meid, Andreas; Müller, Oliver J.; Rizos, Timolaos; Tilemann, Lisa; Haefeli, Walter E.; Burhenne, Jürgen (Analytical chemistry, 2018)
Plasma concentrations of direct oral anticoagulants (DOACs) vary largely between individuals, and they correlate well with desired and adverse outcomes. Although regular concentration monitoring of DOACs is not recommended, information on DOAC exposure could be useful in situations when multiple DOAC-clearance pathways are impaired or nonadherence is suspected. Self-sampling techniques, like the use of dried-blood spots (DBSs), would be particularly useful because they enable the collection of information in ambulatory patients at relevant points in time of the dosing interval (e.g., trough). We developed and validated a DBS-based assay to quantify all currently marketed DOACs (apixaban, dabigatran, edoxaban, and rivaroxaban) in a single ultraperformance-liquid-chromatography-tandem-mass-spectrometry assay. It fulfilled all validation standards within a hematocrit range of 0.33-0.65 and was linear over the calibration ranges of 2.5-750 ng/mL (apixaban and rivaroxaban), 4.4-750 ng/mL (dabigatran), and 9.3-750 ng/mL (edoxaban). Only minor ion suppression (matrix effect ≤13%) was present, inter- and intra-assay precision was ≤13%, and inter- and intra-assay accuracies ranged between 88 and 110%. All DOACs were stable in DBSs up to 52 days at room temperature, if the DBSs were protected from light and humidity. The correlation between (whole blood) DBS and plasma concentrations was assessed in 33 patients under regular DOAC therapy. Deming-regression coefficients between simultaneously collected capillary DBSs and plasma samples were used to predict plasma concentrations from DBSs. Bland-Altman plots revealed a strong agreement between predicted and observed plasma concentrations, thus confirming the suitability of DBSs for DOAC monitoring as an important step toward the important aim of self-sampling at home.